ANEMIC SYNDROME ASSOCIATED TO PARVOVIRUS B19 INFECTION IN PATHOLOGY PREGNANCY WOMEN - Silviya Voleva; Stefka Ivanova; Victor Manolov; Borislav Marinov; Svetla Angelova; Vasil Vasilev; Stoiyan Shishkov (Science & Research)

(untitled)
Viral infections during pregnancy on a world scale are one of the main reasons for severe complications and mortality of the mother and fetus. The post-infectious anemic syndrome is characterized by low serum iron and increased hepcidin, which is the cause for iron accumulation in the endothelial macrophage system and iron deficiency for the needs of erythropoiesis. Probably the increased hepcidin plays a protective role against the growth of microorganisms by reducing extracellular iron. On the other hand, the increased hepcidin may lead to iron deficiency and to inability for effective compensation upon oral supplementation because it suppressed intestinal iron absorption. This study aims to determine the involvement of parvovirus B19 in the anemic syndrome development in the course of/during pathological pregnancy. Materials and Methods: In total 47 serum samples of pregnant women with anemia hospitalized in University Obstetrics and Gynecology Hospital “Maichin Dom”,were tested. Three newborn babies were also included in the study. Serological (ELISA), molecular (PCR), and immunological (CLIA) methods were used. The statistical processing of the results is based on paired Student's t-test and Pearson's correlation. Results and discussion: 9/47 (19.1%) of patients showed presence of B19V-IgM antibodies. B19-IgG antibodies were detected in 19/47 (40.4%) women. The PCR analysis showed presence of viral DNA in all patients with positive B19V-IgM antibodies. B19V-IgM antibodies were proved in one of the newborn and viral DNA was detected. All three babies were positive for B19V-IgG antibodies. In four of the positive patients with the three diagnostic markers for acute infection, the anemia was determined as iron-deficiency according to the low serum levels of hepcidin 2.54 ± 0.4 μg/L compared to control group of pregnant women without anemia (21.7 ± 3.1 μg/L: P<0.001). In the remaining women with a proven acute B19V infection, we found a statistically significant increased level of serum hepcidin (65.3 ± 5.7 μg/L; P<0.001) compared to non anemic pregnant women. Conclusion: Assessment of the frequency and the grade of involvement of parvovirus B19 in the anemic syndrome development during pregnancy and determination of the serum level of hepcidin would contribute to the etiological clarification of the occurred anemic syndrome and would prevent improper iron supplementation by pregnant women.